Linking death registration and survey data: Procedures and cohort profile for The Irish Longitudinal Study on Ageing - Ward, Mark; Kenny, Rose; May, Peter; Normand, Charles; Briggs, Robert (My University, 2020)
Background: Research on mortality at the population level has been severely restricted by an absence of linked death registration and survey data in Ireland. We describe the steps taken to link death registration information with survey data from a nationally representative prospective study of community-dwelling older adults. We also provide a profile of decedents among this cohort and compare mortality rates to population-level mortality data. Finally, we compare the utility of analysing underlying versus contributory causes of death. Methods: Death records were obtained for 779 and linked to individual level survey data from The Irish Longitudinal Study on Ageing (TILDA). Results: Overall, 9.1% of participants died during the nine-year follow-up period and the average age at death was 75.3 years. Neoplasms were identified as the underlying cause of death for 37.0%; 32.9% of deaths were attributable to diseases of the circulatory system; 14.4% due to diseases of the respiratory system; while the remaining 15.8% of deaths occurred due to all other causes. Mortality rates among younger TILDA participants closely aligned with those observed in the population but TILDA mortality rates were slightly lower in the older age groups. Contributory cause of death provides similar estimates as underlying cause when we examined the association between smoking and all-cause and cause-specific mortality. Conclusions: This new data infrastructure provides many opportunities to contribute to our understanding of the social, behavioural, economic, and health antecedents to mortality and to inform public policies aimed at addressing inequalities in mortality and end-of-life care.
PUBLISHED
Keywords: mortality, ageing, death certification, TILDA, data linkage; Ageing